Developing Think Talk Write Strategy on Students’ English Literation Capability - Anita Purba; Semaria Eva Elita Girsang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of developing Think Talk Write (TTW) Strategy in increasing literation capability of English text for 4th semester students of the 2019/2020 academic year of English Study Program, Education Faculty (FKIP) - Simalungun University (USI). The development of the TTW Strategy consists of three phases, namely Think, Talk and the Writing Phase. These three phases are the independent variables of the study, while the dependent variable is literation capability. The research was conducted for 30 students. The sampling technique used saturated sampling technique. The type of data used is primary data. Data were analysed using multiple linear regression analysis method. The results of the analysis show that the Think, Talk and Writing Phases have a positive and significant effect on increasing students’ literation capability in English text, both partially and simultaneously. Thus, it can be concluded that the development of the TTW Strategy has a positive and significant effect in improving students' literation capability.